An Uncommon Presentation of DRESS Syndrome Secondary to Leflunomide Use: A Case Report. (February 2021) - Rao, Suman; Sunkara, Akhila; Srivastava, Nimisha; Sampat, Parth; Ramos, Christopher; Albert, Emily
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a constellation of symptoms that manifest as a result of certain medications. Several antipsychotics, antibiotics, and sulfa-containing drugs are known to be implicated in the etiology of DRESS syndrome. The clinical presentation of this disorder consists of a diffuse rash, lymphadenopathy, and systemic organ damage. Our patient presented with symptoms consistent with DRESS syndrome after being started on leflunomide, which is not commonly associated with DRESS. The diagnostic workup comprised of monitoring inflammatory markers on laboratory work, an excisional lymph node biopsy (to rule out malignancy), and a skin biopsy (to assess the etiology of the rash). Our patient received systemic steroids, dose-adjusted based on expert opinion. Further research is required to explore the association between leflunomide and DRESS and address guidelines for the management of DRESS.